Ratoon rice research: Review and prospect for the tropics - Saito, Kazuki; Dossou-Yovo, Elliott Ronald; Ibrahim, Ali (Elsevier, 2024)
Context: With increasing labor shortage and production costs, water scarcity and climate change, there is increased interest in ratooning as a green, resource-efficient technology to boost sustainable rice production, especially in China. Since the performance of ratoon rice (regenerating a second crop from the stubble left in the fields after the main harvest) and the impact of agronomic practices on its yield have shown mixed results across the world, a better understanding is needed to determine under which conditions ratoon rice performs well. Objective: The objectives are (i) to quantify variation in rice yield of main and ratoon crops, (ii) to assess genetic variation in and impact of agronomic practices on rice yield, focusing on the yield of ratoon crop and total yield (main and ratoon crops), and (iii) review of economic and environmental benefits of ratoon rice in comparison with single and double rice cropping. Methods: In researching ratoon rice, we compiled a database from 68 studies published from 2000 to 2023. Descriptive data analysis was performed. Results: Studies from non-tropical regions account for about 70%. Large variation exists in the yield of ratoon crop across the studies, with lower yield from the tropics than non-tropics. The ratio of yield of ratoon crop to that of main crop also varied widely from 0.13 to 0.67 with 0.36 and 0.5 in tropics and non-tropics, respectively. The yield of ratoon crop was positively related to the yield of main crop, crop duration and nitrogen fertilizer application rate, which were generally higher in non-tropics. Hybrid varieties out-yielded inbred varieties in both main and ratoon crops in non-tropical regions. Direct seeding and AWD had a positive impact on the yield of ratoon crop. The impact of stubble cutting height was mixed. While agronomic nitrogen use efficiency (AEN) during entire ratoon rice cropping was similar to that reported for single rice cropping in previous studies, AEN for ratoon crop in tropical regions tended to be lower than those from previous studies on single rice cropping. Ratoon rice cropping reduced labor input and production cost and increased net economic return compared with double rice cropping. Conclusions: We propose a research agenda, with the focus on improvement of genetic and agronomic practices to explore the potential of ratoon rice cropping, especially in the tropics. Implications: This study provides insight into the progress in ratoon rice research over the past two decades globally, and specifically in the tropics.